InsideDarkWeb.com

Temperature evolution of a Heated Sphere (high Biot number)

A homogeneous sphere is uniformly heated (or cooled) while the boundary is kept at constant temperature.

How does its temperature evolve in time and how is it distributed spatially?

Physics Asked on November 21, 2021

1 Answers

One Answer

(In P.SE tradition I'll provide my own answer to this question)

Newton's Law of heating or Fourier's Heat Equation?

$$text{Bi}=frac{Rh}{k}$$

(where $R$ is the radius, $h$ the convection coefficient and $k$ the thermal conductivity) internal temperature gradients $frac{partial u}{partial r}$ will be small and Newton's Law of heating (so-called 'lumped thermal analysis') can be used.

  • But when $text{Bi}$ is high, spatial temperature distribution becomes uneven and we need to use Fourier's Law of heat conduction.

For a sphere with complete symmetry, we're looking for a function $u(r,t)$ that satisfies:

$$frac{partial u}{partial t}=frac{alpha}{r^2}frac{partial}{partial r}Big(r^2frac{partial u}{partial r}Big)+q$$ with $q$ the heat source. Boundary and initial condition: $$u(R,t)=0text{ and }u(r,0)=f(r)$$ (Attentive readers may now wonder about a 'missing' boundary condition) where $alpha$ is the thermal diffusivity: $alpha=frac{k}{rho c_p}$.

Developed and using shorthand: $$u_t=frac{2alpha}{r}u_r+alpha u_{rr}+qtag{1}$$ The problem now is that $(1)$ is not homogeneous, so separation of variables doesn't work here.

To try and homogenise it we define: $$u(r,t)=u_E(r)+v(r,t)$$ where $u_E(x)$ is the steady state temperature, for $u_t=0$: $$u_t=0 Rightarrow u_E(r)$$ From $(1)$: $$alpha ru''_E+2alpha u'_E+qr=0$$ Which solves to: $$u_E(r)=frac{c_1}{r}+c_2-frac{qr^2}{6alpha}$$ Note that: $$rto 0 Rightarrow u_E(0)to +infty Rightarrow c_1=0$$ (this was our 'hidden' boundary condition) $$r=Rrightarrow u_E(r)=frac{q}{6alpha}(R^2-r^2)$$ Now remember that: $$u(r,t)=u_E(r)+v(r,t)tag{2}$$ Let's calculate some derivatives: $$u_t=0+v_t$$ $$u_r=u'_E(r)+v_r$$ $$u_{rr}=u''_E(r)+v_{rr}$$ $$u'_E=-frac{qr}{3alpha}Rightarrow u''_E=-frac{q}{3alpha}$$ Insert it all into $(2)$: $$u_t=frac{2alpha}{r}(-frac{qr}{3alpha}+v_r)+alpha(-frac{q}{3alpha}+v_{rr})+q$$ $$Rightarrow v_t=frac{2alpha}{r}v_r+alpha v_{rr}$$ So the PDE in $v(x,t)$ is homogeneous. Checking also the boundary condition:

$$u(R,t)=u_E(R)+v(R,t)=0text{ with } u(R,t)=0 Rightarrow v(R,t)=0$$

So the boundary condition remain homogeneous.

Separation of variables can now be executed. Ansatz: $$u(r,t)=R(r)Theta(t)$$ $$frac{Theta'}{alpha Theta}=frac{R''}{R}+frac{R'}{rR}=-lambda^2$$ $$frac{Theta'}{alphaTheta}=-lambda^2$$ $$Theta(t)=exp(-alphalambda^2 t)$$ $$frac{R''}{R}+frac{R'}{rR}=-lambda^2$$ $$rR''(r)+R'(r)+lambda^2rR(r)=0$$ This solves to: $$R(r)=c_1J_0(lambda r)+c_2Y_0(lambda r)$$ Where $J_0$ and $Y_0$ are the Bessel functions.

Note that for: $$r to 0 Rightarrow Y_0 to -infty Rightarrow c_2=0$$ $$R(R)=0=J_0(lambda_n R)$$ $$lambda_n R=z_n$$ The roots $z_n$ of the first Bessel function are:

Roots of Bessel function $$R(r)=c_1J_0(lambda_n R)$$ $$u_n(r,t)=C_nexp(-alphalambda_n^2 t)J_0(lambda_n R)$$ With the superposition Principle: $$u(r,t)=displaystylesum_{n=1}^{infty} C_nexp(-alphalambda_n^2 t)J_0(lambda_n R)$$ Initial condition: $$u(r,0)=u_E(r)+v(r,0) Rightarrow v(r,0)=f(r)-u_E(r)$$ $$v(r,0)=f(r)-u_E(r)=displaystylesum_{n=1}^{infty} C_nJ_0(lambda_n R)$$ So that: $$C_n=frac{2}{R}int_0^R[f(r)-u_E(r)]J_0(lambda_n R)text{d}r$$ Putting it all together: $$boxed{u(r,t)=frac{q}{6alpha}(R^2-r^2)+displaystylesum_{n=1}^{infty} C_nexp(-alphalambda_n^2 t)J_0(lambda_n R)}$$

Answered by Gert on November 21, 2021

Add your own answers!

Related Questions

Measuring the one-way speed of light?

2  Asked on November 29, 2020 by user276997

     

Quantum information = quantum gravity?

1  Asked on November 29, 2020 by redhood

   

Skyrmion number

1  Asked on November 28, 2020 by eric-z

   

The travel of soundwaves

1  Asked on November 28, 2020 by 00xxqhxx00

     

Ask a Question

Get help from others!

© 2021 InsideDarkWeb.com. All rights reserved.